IL-33–Responsive Innate Lymphoid Cells Are an Important Source of IL-13 in Chronic Rhinosinusitis with Nasal Polyps - Shaw, Joanne L.; Fakhri, Samer; Citardi, Martin J.; Porter, Paul C.; Corry, David B.; Kheradmand, Farrah; Liu, Yong-Jun; Luong, Amber (American journal of respiratory and critical care medicine, 2013)
Chronic rhinosinusitis (CRS) without nasal polyps (CRSsNP) and CRS with nasal polyps (CRSwNP) are associated with Th1 and Th2 cytokine polarization, respectively; however, the pathophysiology of CRS remains unclear. The importance of innate lymphoid cells in Th2-mediated inflammatory disease has not been clearly defined. The objective of this study was to investigate the role of the epithelial cell-derived cytokine IL-33 and IL-33-responsive innate lymphoid cells in the pathophysiology of CRS. Relative gene expression was evaluated using quantitative real-time polymerase chain reaction. Innate lymphoid cells in inflamed ethmoid sinus mucosa from patients with CRSsNP and CRSwNP were characterized using flow cytometry. Cytokine production from lymphoid cells isolated from inflamed mucosa of patients with CRS was examined using ELISA and intracellular cytokine staining. Elevated expression of ST2, the ligand-binding chain of the IL-33 receptor, was observed in inflamed sinonasal mucosa from CRSwNP compared with CRSsNP and healthy control subjects. An increased percentage of innate lymphoid cells was observed in inflamed sinonasal mucosa from CRSwNP compared with CRSsNP. ST2(+) innate lymphoid cells are a consistent source of IL-13 in response to IL-33 stimulation. Significant induction of IL-33 was observed in epithelial cells derived from patients with CRSwNP compared with patients with CRSsNP in response to stimulation with Aspergillus fumigatus extract. These data suggest a role for sinonasal epithelial cell-derived IL-33 and an IL-33-responsive innate lymphoid cell population in the pathophysiology of CRSwNP demonstrating the functional importance of innate lymphoid cells in Th2-mediated inflammatory disease.